If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -8 = 4x + -8 Reorder the terms: -8 + 9x = 4x + -8 Reorder the terms: -8 + 9x = -8 + 4x Add '8' to each side of the equation. -8 + 8 + 9x = -8 + 8 + 4x Combine like terms: -8 + 8 = 0 0 + 9x = -8 + 8 + 4x 9x = -8 + 8 + 4x Combine like terms: -8 + 8 = 0 9x = 0 + 4x 9x = 4x Solving 9x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9x + -4x = 4x + -4x Combine like terms: 9x + -4x = 5x 5x = 4x + -4x Combine like terms: 4x + -4x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| x^2-2mx-m=0 | | (32-5)2+2x=6 | | 4x+2x-10=3x+14 | | 5n+20=2n+34 | | 25x=4y+7 | | -2x-5=9x-17 | | 5x+x+(9x-5)=565 | | (2-3x^2)(x^3+8)=0 | | 6x(3)-25x=0 | | 9.6*57.6= | | 10x+4=4x+28 | | 7-(-5)-8+2= | | 4+9b=472 | | S=100+96t-16t^2 | | 5(-9+7x)=305 | | 10x+18=3(3x+3) | | -5(-7x-8)=40 | | 5y+6=4+30 | | 7x-9=-10+x | | 6*(x+3)=8 | | 2x-15=-6 | | 12x=6x+3y | | 19x^2+22x-41=0 | | 4x+ax=3 | | x^2-11x+27=0 | | 14+5n=-4n+5 | | -5.5+-1.5y+2x=-6 | | 2x-3(-4)=-6 | | 4(x-6)=60 | | 5x-8=25x+4 | | -21b^6+9b^4-49b^2=0 | | 7+2w=104 |